Antecedents of Whistleblowing Intentions: Evidance in Local Government Agencies - Nanang Shonhadji (AKRUAL: JURNAL AKUNTANSI, 2022)
This study aims to analyze the relation of attitude, ethical climate-principle, perceived behavioral control, and personal cost on whistleblowing intention with organizational commitment as a moderating variable. This study uses the moderating regression analysis method. The sample used is employees who work in the Office of the Inspectorate and the Regional Finance and Revenue Management Agency (BPKPD) of Pasuruan Regency. The variables of attitude and perceived behavioral control have a positive effect on whistleblowing intention, the variable of ethical climate principle has no effect on whistleblowing intention, and the variable of personal cost has a negative effect on whistleblowing intention as the results of this study. Further results also inform that the variable of organizational commitment as moderating variable and strengthen the role of the theory of planned behavior in shaping a government apparatus intention as a whistle blower.